Sensitivity analysis of loss resistances variations of PV generators applied to the assessment of maximum power point changes due to degradation. (August 2021) - Carrero, C.; Ramirez, D.; Rodríguez, J.; Castillo-Sierra, R.
Abstract: During their lifespan, due to small but persistent changes in their physical-chemical properties, photovoltaic (PV) generators undergo processes that degrade their electrical properties and reduce the power they can deliver. This power loss has technical and economic consequences, so it is of great interest to know their causes and develop procedures to assess its impact. This work proposes an assessment of the probable displacement of the maximum power point of mono and polycrystalline silicon PV modules and generators, before degradation and aging processes start. For this purpose, it is considered that the changes that these processes cause in the generators I–V characteristic are the result of variations of their loss resistances. To achieve this, a sensitivity analysis is carried out to study how the variations in the loss resistances affect the maximum power voltage and current. From the results of this analysis and based on the coefficients of sensitivity, a procedure using a simple linear approximation, which assesses the values towards which the maximum power voltage and current of PV generators will evolve, is proposed. The obtained results show differences lower than 1% concerning the actual displacements, even for the worst case, despite the apparent simplicity of the proposed procedure. Highlights: Degradation and aging undergone by PV generators deteriorate the I–V curve. Deterioration of the I–V curve is related to variations of the loss resistances. The effects of the variations of loss resistances are studied by a sensitivity analysis. Sensitivity coefficients are used to obtain new maximum power point values. Calculations made by a simple linear approximation provide errors of less than 1%.